Case Report: Lessons Learned From Aortic Valve Rupture After Blunt Chest Trauma - Zhao, Qu-ming; Lai, Ling-yu; He, Lan; Liu, Fang (Frontiers in Pediatrics, 2021)
Aortic valve rupture (AVR) due to blunt chest trauma is extremely rare in the pediatric population, and little attention has been paid to such damages. Early diagnosis of AVR may not be easy in patients with multiple competing injuries and poor acoustic windows. We report a case of delayed diagnosis of AVR in a 12-year-old boy after falling from a height of 15 meters, who presented with recurrent hemoptysis and ventilator dependence. This rare case highlights the importance of performing transesophageal echocardiography in trauma patients when the images of transthoracic echocardiography are suboptimal, especially for those presenting with signs and symptoms suggestive of heart failure. The overall prognosis of aortic valve replacement is good.